High yield of HIV testing in dengue-like febrile illness in Singapore - Verrall, Ayesha J. (2019)
Where dengue virus infections are endemic, acute febrile illness is often managed as dengue fever (DF) without diagnostic testing. In a prospective study of 140 patients with clinical features of DF, 3 (2.1%) had acute HIV infection (AHI). We recommend testing for AHI in dengue-like febrile illness.